A job task analysis to describe the physical demands of specialist paramedic roles in the National Ambulance Resilience Unit (NARU). - Rue, Carla A.; Rayson, Mark P.; Walker, Ella F.; Doherty, Julianne; Thompson, Jane; Myers, Stephen D.; Blacker, Sam D.; Milligan, Gemma S.; Brown, Pieter E.H.; Siddall, Andrew G. (Work, 2019)
BACKGROUND: The National Ambulance Resilience Unit (NARU) works on behalf of each National Health Service (NHS) Ambulance Trust in England to strengthen national resilience and improve patient outcome in challenging pre-hospital scenarios. OBJECTIVE: To conduct a Job Task Analysis and describe the physical demands of NARU roles. METHODS: A focus group was conducted to describe the physically demanding tasks performed by NARU personnel. Subsequently, the physical demands of the identified tasks were measured in 34 NARU personnel (29 male and 5 female). RESULTS: Eleven criterion tasks were identified; Swift Water Rescue (SWR), Re-board Inflatable Boat (RBIB), Set up Decontamination Tent (SDT), Clinical Decontamination (CD), Movement in Gas Tight Suits (MGTS), Marauding Terrorist Fire Arms (MTFA), Over Ground Rescue (OGR), Unload Incidence Response Unit Vehicle (UIRUV), Above Ground Rescue (AGR), Over Rubble Rescue (ORR) and Subterranean Rescue (SR). The greatest cardiovascular strain was measured during SWR, MGTS, and MTFA. The most thermally challenging tasks were the MTFA, CD, SR and OGR. The greatest muscular strength requirements were during MTFA and OGR. CONCLUSIONS: All five components of fitness (aerobic endurance, anaerobic endurance, muscular strength, muscular endurance and mobility) were required for successful completion of the physically demanding tasks performed by NARU personnel.